Sustainable Upcycling of Fisheries and Aquaculture Wastes Using Fish-Derived Cold-Adapted Proteases - Khiari, Zied (Frontiers in Nutrition, 2022)
The fisheries and aquaculture industries are some of the major economic sectors in the world. However, these industries generate significant amounts of wastes that need to be properly managed to avoid serious health and environmental issues. Recent advances in marine waste valorization indicate that fish waste biomass represents an abundant source of high-value biomolecules including enzymes, functional proteins, bioactive peptides and omega-3 rich oils. Enzyme-assisted processes, for the recovery of these value-added biomolecules, have gained interest over chemical-based processes due to their cost-effectiveness as well as their green and eco-friendly aspects. Currently, the majority of commercially available proteases that are used to recover value-added compounds from fisheries and aquaculture wastes are mesophilic and/or thermophilic that require significant energy input and can lead to unfavorable reactions (i.e., oxidation). Cold-adapted proteases extracted from cold-water fish species, on the other hand, are active at low temperatures but unstable at higher temperatures which makes them interesting from both environmental and economic points of view by upcycling fish waste as well as by offering substantial energy savings. This review provides a general overview of cold-adapted proteolytic enzymes from cold-water fish species and highlights the opportunities they offer in the valorization of fisheries and aquaculture wastes.